Economic Prospects of Mosque-Based Publicity: Study On Sharia Cooperation BMT Congregation Of Al Isyah Hakim Mosque Namurambe - Burhanuddin Al Butary; Ratna Sari Dewi; Cynthia Syahni (Journal of Global Islamic Economic Studies, 2023)
This research aims to examine how the contribution of mosque functions can be improved, not just limited to activities. only worship but can also empower the economy of mosque congregations by establishing Baitul Maal wal Tamwil. Researchers' findings from a literature review show that the establishment of mosque-based BMT can significantly improve the congregation's economy. The research design carried out was by going directly to the BMT Al Issyah Hakim Namurambe Mosque Sharia Cooperation field, then strengthening it by collecting articles related to the researcher's theme which were downloaded from Google Scholar for publication in the last 5 years and then sorting them according to the Researcher's Discussion Topic. namely the BMT Strategy in Empowering a Mosque-Based Economy so that 41 articles were obtained. The BMT strategy used was: ZISWAF for Economic Empowerment, Human Resources, Transparency and Accountability, Financial Inclusion, Marketing Management, Implementation of the Economic Sharia Agreement, BMT Performance, Establishment of BMT, ZISWAF integration with BMT, Role Models. This research aims to explore the economic prospects of mosque-based society by the congregation of the Al IssyAH Hakim Namurambe mosque. The research carried out is classified as field research. That way, research objects are objects in the field that are able to provide information about research studies. This type of research is descriptive field research with a qualitative approach. The output produced is a national journal and other proceedings. The population and samples to be taken have been determined and arranged according to research needs. This research shows that the congregation of the Al Issyah Hakim Namurambe mosque.